2018
DOI: 10.1108/bij-07-2017-0194
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Big Data analytics and data security practices on service supply chain performance

Abstract: Purpose The purpose of this paper is to investigate the effects of Big Data analytics, data security and service supply chain innovation capabilities on services supply chain performance. Design/methodology/approach The paper draws on the relational view of resource-based theory to propose a theoretical model. The data were collected through survey of 145 service firms. Findings The results of this study found that the Big Data analytics has a positive and significant relationship with a firm’s ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 83 publications
5
105
2
Order By: Relevance
“…First, this paper found that firms that uses supply chain analytics were more likely to develop supply chain innovation capabilities. The result is in line with Fernando et al (2018) claims, that Big Data analytics is a strong determinant for supply chain innovative capability. From KBT perspective, this finding suggest supply chain innovation is contingent upon acquiring, transforming, storing information and quantitative analyzing such data.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…First, this paper found that firms that uses supply chain analytics were more likely to develop supply chain innovation capabilities. The result is in line with Fernando et al (2018) claims, that Big Data analytics is a strong determinant for supply chain innovative capability. From KBT perspective, this finding suggest supply chain innovation is contingent upon acquiring, transforming, storing information and quantitative analyzing such data.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, this can be extended via supply chain analytics. Firms can improve innovation in their supply chain with competitive weapons namely; timely and quality data (Fernando et al, 2018). Despite these claims in the liter-ature, the impact of supply chain analytics (SCA) has on supply chain management (SCM) is still an uncharted area (Lai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In banking sectors and retail industries, and in government, big data is applied extensively for analysing spending behaviour of customers, security and fraud detection, sentiment and social network analysis (Kshetri 2014). In addition, big data can help law enforcement agencies to deploy resources more efficiently, respond quickly and increase presence in crime prone areas (Kang, Kim, and Lee 1998;Fernando et al 2018). Big data also enhances retail supply chain, which heavily depends on the availability of accurate and up-to-date information for demand forecast and other business execution (Gunasekaran et al 2017).…”
Section: Big Data Supply Chain Analyticsmentioning
confidence: 99%
“…Kiron et al 2013;cited by Baig et al, 2017) provide a thorough survey of IoT security and privacy challenges from the perspectives of technologies and architecture used. Fernando et al (2018) in their work focussed on IoT intrinsic vulnerability and their implications for the fundamental information security challenges in confidentiality, integrity, and availability. Similarly, Buenrostro et al (2019) and Buenrostro et al (2018) focussed on the social and ethical aspects of drone use and identified key areas of concerns connected with commercial drone use.…”
Section: Article De-selection Criteriamentioning
confidence: 99%
“…Some scholars have conducted researches in the context of sustainability (Darkow et al, 2015;Liu, Bai, Liu and Wei, 2017;Tseng et al, 2018), big data (Fernando et al, 2018;Boone et al, 2018) and demand updating . However, they are yet to consider the influence of behavioural factors.…”
Section: Research Agendamentioning
confidence: 99%